The Effect of Occupation-Based Modified Constraint-Induced Movement Therapy on the Participation of Children with Cerebral Palsy: A Single-Blind Randomized Controlled Trial - Ostadzadeh, Ali; Amini, Malek; Hasani mehraban, Afsoon; Maroufizadeh, Saman; Farajzaheh, Ata (Iranian Journal of Child Neurology, 2023)
Objective This study investigates the impact of modified constraint-induced movement therapy (m-CIMT), accompanied by occupation-based and activity analysis, on the participation of children with hemiplegia. Materials & Methods Twenty-three participants were randomly assigned to the intervention and control groups. The intervention group received occupation-based m-CIMT (m-CIMT along with occupation-based and activity analysis), while the control group received m-CIMT without occupation-based and activity analysis. The intervention was conducted one hour perday, three days a week, for four weeks. Results The primary outcomes revealed no significant differences between groups in promoting the participation of children with hemiplegia in the activities of daily living (ADL). However, scores were higher in the intervention group with a medium to large effect size (Canadian occupational performance measure: F(1,19)=2.14, P=0.160, η2 P=0.101, Canadian occupational performance measure-satisfaction: F(1,19)=1.53,P=0.231, η2 P=0.075, Goal attainment scaling: F(1,19)=5.55, P=0.029, η2 P=0.226). This effect remained during the follow-up period. The secondary outcomes indicated no significant differences between groups in improving the manual ability of the children. However, scores were higher in the intervention group with a medium to large effect size (ABILHAND-Kids: F(1,19)=0.64, P=0.434, η2 P=0.033, pediatric motor activity log- how long: F(1,19)=3.53, P=0.076, η2 P=0.157, pediatric motor activity log- how well: F(1,19)=2.59, P=0.124, η2 P=0.120). This effect was sustainable during the follow-up period. Conclusion m-CIMT accompanied by occupation-based and activity analysis and the client-centered paradigm substantially enhances the manual ability of children with hemiplegia and their participation in the ADL.